Pengaruh Omzet Penjualan Terhadap Laba Sebelum Pajak UMKM Pada Kios Rista Cell Periode 2017-2019 - Ridiana Febrianto; Andri Indrawan; Idang Nurodin (Jurnal Syntax Transformation, 2020)
This study aims to determine the effect of sales revenue on MSME profit before tax on Rista Cell Kiosk, Jampang Kulon District. The population and sample in this study are financial statements namely sales revenue reports and earnings reports before taxes for the period of 2017 to 2019. This research technique uses the classic assumption test, multiple linear regression analysis and hypothesis testing. Data collection techniques using interviews, documentation, data realization (financial statements) and literature studies. After the data is collected, the test analysis in this study was carried out with the help of IBM SPSS 26 for Windows. The test results of multiple linear regression analysis show the equation Y = 89480865,970 + 9,493 which means that if the sales revenue is zero then there is an increase in profits by 89480865, whilst the positive revenue coefficient of sales is 9,493 means that every increase in sales revenue will increase profit by 9,493. While the partial test results (t) show the t(count) of the sales revenue variable (X) that is equal to 4.009 and the t(table) is 2.032245 then the t(count) is 4.099 > t(table) 2.032245 and the significant value is 0.000 < 0.05. As for the level of sales revenue effect on earnings before tax is categorized as weak, this is shown from the results of the coefficient of determination test with an R Square value of 0.331 or 33.1%. It can be concluded that sales revenue affects earnings before tax or the hypothesis is accepted